(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2009)
Clinical Behavior Analysis explains the development and maintenance of behavior through historical and actual environmental variables. With regard to children’s care, the participation of parents is extremely important because they are part of the frame of reference and present congruity for children’s behavior. This case study aimed to evaluate the effect of parental training and behavior intervention in the child’s aggressive behavioral patterns. A nine-year-old boy and his parents underwent treatment. The major complaint was the child’s aggressive behavior and therefore his parents were trained to solve the child’s behavior problems. Changes in the family context, and consequently the client’s behavior, were observed. The frequency of inappropriate behavior decreased and the boy started showing new, appropriate behavior. Such results indicate the importance of changing the child’s environment in order to achieve the desired modification in behavior.